To study the thermal performance of Shell and Tube Heat Exchanger by Using Different TubesMaterials - Ravi Kumar Gupta (AG Volumes, 2021)
In this work, a brief research background is provided over the tube and shell heat exchangers. Heat exchangers are very extensively brought in use for applications like heat transfer in the industries. Tube and shell heat exchanger are among such heat exchangers and provides more areas for transferring heat among the two fluids in comparison with other kinds of heat exchangers. “Tube heat exchanger and shell heat exchanger” are very extensively brought in use for applications like liquid to liquid heat transfer constituting of high-density working flute. The focus of this study is over the utilization of tube and shell heat exchangers with different materials: copper, steel and aluminium. Further with the help of ANSYS, a computational model was implemented for the same heat exchanger. This study has conducted investigations over the tube and shell heat exchanger with assessment off exchanger’s effectiveness and temperature. Steel, copper and aluminum showed effectiveness of 0.738, 0.748 and 0.747 respectively. This result showed that copper has the maximum effectiveness and steel has the lowest effectiveness.